2020
DOI: 10.1128/jcm.00343-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BioFire FilmArray Pneumonia Panel for Detection of Viral and Bacterial Pathogens in Lower Respiratory Tract Specimens in the Setting of a Tertiary Care Academic Medical Center

Abstract: Our objective was to evaluate the diagnostic yield and accuracy of the BioFire FilmArray pneumonia panel (BFPP) for identification of pathogens in lower respiratory tract specimens (n = 200) from emergency department (ED) and intensive care unit (ICU) patients at a tertiary care academic medical center. Specimens were collected between January and November 2018, from patients ≥18 years of age, and culture was performed as part of standard-of-care testing. The BFPP identified a viral or bacterial target in 117/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
81
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 13 publications
10
81
3
3
Order By: Relevance
“…Given this context, the Unyvero HPN Application can be a potential RDT of choice, considering that the HPN panel is able to detect 20 bacterial species, one fungus and 17 antimicrobial resistance genes (Table 1) In our study, the HPN Application detected additional bacterial species among 21/83 (25.3%) samples tested. This finding is in concordance with previous studies that have reported a similar increase in the bacterial yield from LRT samples, using other molecular detection assays among non-COVID-19 patients [13][14][15]. Currently, the clinical implications of detecting additional bacterial species only by the molecular methods (in the absence of culture All rights reserved.…”
Section: Discussionsupporting
confidence: 92%
“…Given this context, the Unyvero HPN Application can be a potential RDT of choice, considering that the HPN panel is able to detect 20 bacterial species, one fungus and 17 antimicrobial resistance genes (Table 1) In our study, the HPN Application detected additional bacterial species among 21/83 (25.3%) samples tested. This finding is in concordance with previous studies that have reported a similar increase in the bacterial yield from LRT samples, using other molecular detection assays among non-COVID-19 patients [13][14][15]. Currently, the clinical implications of detecting additional bacterial species only by the molecular methods (in the absence of culture All rights reserved.…”
Section: Discussionsupporting
confidence: 92%
“…However, respiratory samples are processed in batches usually once every working day for conventional coronavirus PCR diagnostics, thus resulting in long sample to answer times. Alternatively, coronavirus detection is also provided by highly multiplexed, random access PCR platforms more rapidly (19)(20)(21) but these cannot be adapted to the individual diagnostics needs of a patient considering his symptoms and the epidemiology of circulating respiratory viruses. For comparison, the Hologic Panther Fusion (PF) system provides a panel of three CE marked and FDA cleared multiplex real-time PCRs that cover influenza virus A/B (Flu A/B), respiratory syncytial virus (RSV), parainfluenza virus 1-4 (ParaFlu), human metapneumovirus (hMPV), adenovirus (AdV) and rhinovirus (RhV) and can be performed according to the individual diagnostic request.…”
Section: Introductionmentioning
confidence: 99%
“…Specimens were conveyed to the microbiology laboratory where a Fil-mArray Pneumonia Panel plus test (FA-PNEU, BioFire Diagnostics, Salt Lake City, UT, USA) was performed. The FA-PNEU is an automated multiplex PCR test allowing direct detection of 15 bacteria with a semiquantitative value, 3 atypical bacteria, 9 viruses, and 7 antimicrobial resistance genes within 1 h and 15 min [2]. FA-PNEU testing was done 24/7, and results were immediately called to the intensive care physician pursuing antimicrobial optimization.…”
mentioning
confidence: 99%